The potential mechanism of postoperative cognitive dysfunction in older people - Lin, Xianyi; Chen, Yeru; Zhang, Piao; Chen, Gang; Zhou, Youfa; Yu, Xin (Experimental gerontology, 2020)
Postoperative cognitive dysfunction (POCD) is a common disorder following surgery, which seriously threatens the quality of patients' life, especially the older people. Accumulating attention has been paid to POCD worldwide in pace with the popularization of anesthesia/surgery. The development of medical humanities and rehabilitation medicine sets higher demands on accurate diagnosis and safe treatment system of POCD. Although the research on POCD is in full swing, underlying pathogenesis is still inconclusive due to these conflicting results and controversial evidence. Generally, POCD is closely related to neuropsychiatric diseases such as dementia, depression and Alzheimer's disease in molecular pathways. Researchers have come up with various hypotheses to reveal the mechanisms of POCD, including neuroinflammation, oxidative stress, autophagy disorder, impaired synaptic function, lacking neurotrophic support, etc. Recent work focused on molecular mechanism of POCD in older people has been thoroughly reviewed and summed up here, concerning the changes of peripheral circulation, pathological pathways of central nervous system (CNS), the microbiota-gut-brain axis and the related brain regions. Accordingly, this article provides a better perspective to understand the development situation of POCD in older people, which is conductive to uncover the pathological mechanism and exploit reasonable treatment strategy of POCD. •Postoperative cognitive dysfunction (POCD) is a common complication after surgery with a high prevalence in older people.•Peripheral changes such as inflammation and immune activation are related to POCD in older people.•Central response of glial cells, neurotoxic changes and neurotrophic feebleness are involved in POCD of older people.•The microbiota-gut-brain axis plays a role in the development of POCD in older people.•Brain regions such as hippocampus, prefrontal lobes and cingulate gyrus play important roles in POCD of older people.